Education and training in end of life care for health and social care professionals in north west England. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Duxbury, Joy; Obrien, Teri; Pulsford, Dave; Yates, Sue
Abstract : Background: Education and training in end-of-life care is recommended for health and social care staff at a range of levels. Such education should embrace an understanding of contemporary policy, best practice initiatives, care pathways and key interpersonal skills. Aims of study: To scope the nature and content of education and training in end-of-life care for health and social care professionals in one region of England; To identify gaps in existing provision and priorities for future educational initiatives. Methods: An online survey of University-based educational provision in North-West England (n=7 Universities) and health and social care provider-based training initiatives (n=48 provider organisations); An online survey of health and social care professionals (n=446) to ascertain their views regarding their preparedness for delivering end-of-life care and perceived gaps in their education and training; Focus groups of health and care staff (n=21); people receiving end-of-life care (n=16) and carers of such people (n=16) to provide further information regarding staff's preparedness for end-of-life care and education and training needs. Results: Education and training was wide-spread but varied widely in extent and content. Key learning methods were discourse and discussion but skills' training was less formally evident. Contemporary best practice and policy initiatives were widely but not universally addressed. Staff's preparedness for end-of-life care varied with role but many staff identified additional learning needs, particularly those is non-specialist roles. Awareness of policy and best practice was not universal. Patients and carers reported mixed experiences of care which they perceived to be the result of poor skills preparation, attitudinal barriers and a lack of co-ordination. Conclusion: While much education and training related to end-of-life care is on offer in North West England, best practice is not always being addressed. Staff overall require greater awareness of contemporary policy and practice initiatives and enhanced interpersonal skills.